Endoscopic ultrasound-guided right hepaticoduodenostomy for a patient with Chilaiditi syndrome - Kobashi, Ryoichiro; Suzuki, Rei; Takagi, Tadayuki; Sugimoto, Mitsuru; Konno, Naoki; Hikichi, Takuto; Ohira, Hiromasa (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Kobashi R, Suzuki R, Takagi T, Sugimoto M, Konno N, Ohira H. Endoscopic ultrasound-guided right hepaticoduodenostomy for a patient with Chilaiditi syndrome. Turk J Gastroenterol 2018; 29: 239-40.